Compensatory life‐history responses of a mesopredator may undermine carnivore management efforts - Minnie, Liaan; Gaylard, Angela; Kerley, Graham I. H; Chapron, Guillaume (The Journal of applied ecology, 2016)
Lethal carnivore management, aimed at reducing carnivore impacts, is a global phenomenon threatening the persistence of many carnivores. Black‐backed jackals Canis mesomelas, the dominant cause of livestock predation in southern Africa, are widely hunted to reduce livestock predation. Despite centuries of lethal management, jackals persist. Smaller canids, like jackals, are highly adaptable and display variable responses to mortality sources, which may affect management outcomes. The effects of killing carnivores will depend on their behaviour, social organization, reproduction and dispersal patterns. We predicted that hunted jackals will alter demographic and reproductive patterns to compensate for increased mortality. Here, we collected demographic and reproductive information from harvested jackals and compared it between continually hunted (farms) and unmanaged populations (reserves). The removal of jackals from farms results in a decrease in median age from 5–6 years (reserves) to 2–3 years (farms). Hunting also changed the age structure of jackal populations from a stable population to an expanding population. This may be ascribed to the compensatory immigration of individuals from neighbouring unmanaged areas, suggesting the formation of a source–sink system. Unmanaged areas may act as source populations exporting young, dispersing individuals to hunted areas which may act as sinks. This is likely driven by disruptions in the normal, mutually exclusive territorial system resulting in low densities of conspecifics on farms. The low density of conspecifics allows younger individuals that would be socially precluded from reproducing to reproduce. Jackals on farms compensated for increased mortality by increasing the pregnancy rate of young individuals and increasing the litter size at younger ages, thereby increasing reproductive output. Synthesis and applications. The lethal management of predators is the prevailing strategy to reduce livestock predation. However, the highly adaptable nature of jackals and the combination of compensatory mechanisms such as increased reproduction and potential for immigration allow these predators to persist in the face of severe anthropogenic mortality, possibly through the formation of a source–sink system. These compensatory processes will continue to counter population management actions as long as recruitment from unmanaged areas persists.